Post-Combustion CO2 Capture with Monoethanolamine in a Combined-Cycle Power Plant: Exergetic, Economic and Environmental Assessment - Petrakopoulou, Fontina; Tsatsaronis, George; Boyano, Alicia; Morosuk, Tatiana (IntechOpen, 2012)
None